Desain Pembelajaran Buku Ajar Bahasa Arab Berbasis Permainan Edukatif Untuk Meningkatkan Keterampilan Menyimak - Wildan Khoirun Ni'am; Aufia Aisa (Al-Lahjah, 2023)
This research is motivated by the lack of MA Al-Bairuny Jombang students in mastering Arabic listening material so that it affects the low interest and learning achievement. This is because the learning process that takes place is only done conventionally which in the end causes students to tend to be passive and easily bored in learning Arabic. Therefore, this research aims to develop an Arabic textbook based on an educational game of listening to Arabic as a solution to overcome the lack of mastery of listening and listening to students' Arabic sentences. The method used in this research is R&D by adopting the ADDIE model. The subjects in this study were students of class XI IPS 2 MA Al-Bairuny Jombang, totaling 22 children. Data collection instruments used in the form of interviews, questionnaires and tests. The types of data analyzed to produce qualitative and quantitative data include: 1) teaching materials have been developed in the form of Arabic language textbooks based on listening to Arabic educational games. 2) based on the validity test, the textbook developed reached a very valid feasibility level with an average of 93.33% from material experts and 83.57% from media experts. 3) the level of effectiveness of the textbooks is very effective, seen from the comparison of the pre-test scores reaching an average of 76% and the post-test reaching an average of 84%. Abstrak Penelitian ini dilatarbelakangi oleh minimnya para siswa MA Al-Bairuny Jombang dalam menguasai materi menyimak bahasa Arab sehingga berpengaruh pada rendahnya minat serta prestasi belajar. Hal ini dikarenakan proses pembelajaran yang berlangsung hanya dilakukan secara konvensional yang pada akhirnya menyebabkan peserta didik cenderung pasif dan mudah bosan dalam pembelajaran bahasa Arab. Oleh karena itu, dilakukannya penelitian ini bertujuan untuk mengembangkan buku ajar bahasa Arab berbasis permainan edukatif menyimak bahasa Arab sebagai solusi untuk mengatasi minimnya penguasaan mendengar dan menyimak kalimat bahasa Arab peserta didik. Metode yang digunakan dalam penelitian ini adalah R&D dengan mengadopsi model ADDIE. Subjek dalam penelitian ini adalah peserta didik kelas XI IPS 2 MA Al-Bairuny Jombang yang berjumlah 22 anak. Instrumen pengumpulan data yang digunakan berupa interview, kuisioner dan tes. Adapun jenis data yang dianalisis  menghasilkan data kualitatif dan kuantitatif diantaranya: 1) telah dikembangkan bahan ajar berupa buku ajar bahasa Arab berbasis permainan edukatif menyimak bahasa Arab. 2) berdasarkan uji valididtas, buku ajar yang dikembangkan mencapai tingkat kelayakan sangat valid dengan rata-rata 93,33% dari ahli materi dan 83,57% dari ahli media. 3) tingkat keefektivan buku ajar adalah sangat efektiv dilihat dari perbandingan nilai pre-test mencapai rata-rata 76% dan post-test mencapai ratarata 84%.